2019
DOI: 10.1080/10669817.2019.1673953
|View full text |Cite
|
Sign up to set email alerts
|

The effect of real-time feedback on learning lumbar spine joint mobilization by entry-level doctor of physical therapy students: a randomized, controlled, crossover trial

Abstract: Objective: To examine the effects of real-time, objective feedback on learning lumbar spine joint mobilization techniques by entry-level Doctor of Physical Therapy (DPT) students. Methods: A randomized, controlled, crossover design was used. Twenty-four 1st Year DPT students were randomized into two groups. Group 1 (n = 12) practiced with the real-time feedback device first and then without it, while Group 2 (n = 12) practiced without the device first and then with it. Both practice periods with and without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The literature search was updated on June 30, 2021, and led to the identification of three additional articles fulfilling the inclusion criteria. Forty-six studies were deemed relevant and were included in this review ( 7 12 , 15 54 ). The literature search also revealed seven literature reviews from which no additional original studies were identified ( 2 , 6 , 55 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search was updated on June 30, 2021, and led to the identification of three additional articles fulfilling the inclusion criteria. Forty-six studies were deemed relevant and were included in this review ( 7 12 , 15 54 ). The literature search also revealed seven literature reviews from which no additional original studies were identified ( 2 , 6 , 55 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies and both quantitative and qualitative data are reported in Supplementary Table 1 and visually presented in Figure 2 . From the 46 included studies, 20 (43.5%) used a device to measure SMT or MOB force-time characteristics at the clinician-patient interface ( 7 , 11 , 12 , 24 , 26 , 28 31 , 37 , 39 , 40 , 44 , 46 52 ), 23 (50%) at the patient-table interface ( 9 , 10 , 15 23 , 25 , 27 , 32 36 , 38 , 42 , 45 , 53 , 54 ), and 3 (6.5%) at both interfaces ( 8 , 41 , 43 ). A total of 10 different devices measured SMT/MOB force-time characteristics at clinician-patient interfaces and 6 at patient-table interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations